2013
DOI: 10.5194/bg-10-2583-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dust deposition on dissolved trace metal concentrations (Mn, Al and Fe) during a mesocosm experiment

Abstract: The deposition of atmospheric dust is the primary process supplying trace elements abundant in crustal rocks (e.g. Al, Mn and Fe) to the surface ocean. Upon deposition, the residence time in surface waters for each of these elements differs according to their chemical speciation and biological utilization. Presently, however, the chemical and physical processes occurring after atmospheric deposition are poorly constrained, principally because of the difficulty in following natural dust events in situ. In the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 90 publications
5
63
0
Order By: Relevance
“…For the carbonated dust studied in this paper, we do not have enough data to clearly attribute the origin of the dissolved aluminium and iron to a specific solid phase, but a noticeable solubility increase at pH 3 might attribute a part of soluble aluminium and iron to carbonated phases. We can compare the solubility found here with that estimated and calculated in seawater during the DUNE mesocosm experiments, where the same soil fraction was used, but only after processing with synthetic cloud-like water to reproduce condensation-evaporation processes on dust particles during atmospheric transport (Wuttig et al, 2013). For manganese, iron, and aluminium, these authors reported sol- ubilities that are respectively equal to 27-41, 0.12, and 1 %.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…For the carbonated dust studied in this paper, we do not have enough data to clearly attribute the origin of the dissolved aluminium and iron to a specific solid phase, but a noticeable solubility increase at pH 3 might attribute a part of soluble aluminium and iron to carbonated phases. We can compare the solubility found here with that estimated and calculated in seawater during the DUNE mesocosm experiments, where the same soil fraction was used, but only after processing with synthetic cloud-like water to reproduce condensation-evaporation processes on dust particles during atmospheric transport (Wuttig et al, 2013). For manganese, iron, and aluminium, these authors reported sol- ubilities that are respectively equal to 27-41, 0.12, and 1 %.…”
Section: Resultsmentioning
confidence: 62%
“…It is important to keep in mind that the calculated solubilities in the mesocosms were marred by a significant uncertainty. The average solubility similarities obtained from unprocessed dust at pH 3 in water (this study) and cloud-processed dust in seawater (Wuttig et al, 2013) indicate that the acidic conditions encountered during the laboratory cloud processing (see Guieu et al, 2010) were recorded in the dust until it was used to seed the mesocosms. This recorded acidity controlled the solubility levels in seawater.…”
Section: Aghnatios Et Al: a Fine Fraction Of Soil Used As An Aeromentioning
confidence: 62%
“…Those results were satisfactorily simulated with a one-dimensional model of the Fe biogeochemical cycle, coupled with a simple ecosystem model (Ye et al 2011). When a second dust wet deposition was simulated, iron dissolution from the dust particles was then evidenced due to the excess Fe binding ligand concentrations produced by the enhanced biological activity (Wuttig et al 2013). When simulating dust wet deposition at least a doubling of Chla (mainly attributed to small phytoplankton (<3 μm); Giovagnetti et al 2013) was observed but the Chla concentrations remained very low (maximum values 0.22 μg L-1) maintaining the oligotrophic status of the tested waters .…”
Section: Experimental: In Situ Mesocosmsmentioning
confidence: 91%
“…Initial conditions indicate (1) very low dissolved inorganic phosphorus concentrations ([DIP]) (5 ± 3 nM; PulidoVillena et al, 2014), (2) dissolved inorganic nitrogen concentrations ([DIN]) below the detection limit (< 30 nM; Ridame et al, 2013), and (3) dissolved iron concentrations ([DFe]) typical of coastal area (3.3 ± 0.8 nM; Wuttig et al, 2013). Following the first seeding, a decrease in [DFe] due to scavenging by sinking dust (Wuttig et al, 2013) and a transient increase in [DIP] were observed.…”
Section: Evolution Of the Physical And Biogeochemical Parametersmentioning
confidence: 99%